Implementasi Kegiatan Rehabilitasi Rumah Layak Huni di Kota Pekanbaru - Occi Mardila Purwanti; Sujianto Sujianto (Jurnal Relasi Publik, 2023)
This research is motivated by the delay in fund disbursement, the lack of performance of the implementers and socialization to the community is still not optimal. This research aims to find out the implementation of livable house rehabilitation activities in Pekanbaru City. This research uses a descriptive qualitative method, with data collection techniques of observation, interviews and documentation. This research uses the theory of Charles O. Jones in Siti Erna (2009) with three indicators, namely: organization, interpretation and application. Based on the results of the research, it can be concluded that the implementation of livable house rehabilitation activities has not run optimally. This is because there are still misunderstandings between parties due to lack of coordination, the performance of the implementers is still not optimal, lack of socialization and delays in disbursement of funds, and development exceeds the target time. Suggestions from this study are to improve coordination and cooperation between parties and carry out their duties properly, need to hold socialization again, additional funds and construction can be completed on time.